STUDI TENTANG MOTIF, WARNA DAN TEKNIK BATIK KERINCI DI KOTA SUNGAI PENUH - SUCI PERMATA SARI, Drs. Erwin, M.Sn, Drs. Ajusril S (Serupa The Journal of Art Education, 2014)
This study aims to Describe: the form of motive 1), staining 2), and the technique 3) of batik Kerinci. This research is descriptive qualitative. The data sources are the primary source directly by the informant, source data taken in the form of written notes (image recording) derived from informants interviewed, documentation and literature study. Kerinci motif derived from the shape of the flora, fauna and writing (literacy) incung, Kerinci batik colors have a tendency to dark colors such as dark red and black, the technique used is the technique of batik and batik techniques.Kata kunci: Motif, Warna, Teknik, Batik